Sosialiasi Pembuatan Minuman Jahe Instan di Desa Sukodadi Kecamatan Paiton Kabupaten Probolinggo - Utami Ratna Swari (Abdi Panca Marga, 2021)
KKN Thematic Covid-19 using theme Empowering the Community in the Period of Covid-19 Pandemic is a service done by university students that is expected to empower the community by utilizing their knowledge, especially in the period of Covid-19 pandemic. One of the programs of KKN Thematic Covid-19 is giving socialization in the making of instant ginger drink. Instant ginger drink is a processed product of ginger crystallization by boiling it with water, sugar, salt, cinnamon, lemongrass and clove. Realizing the high amount of potential health and nutrition of ginger, KKN Panca Marga University Probolinggo team in Paiton district make initiation to give socialization in the making of instant ginger drink. The program is done in four (4) days, the first day is the introduction of ingredients and tools, the second and the third day is the making of instant ginger drink and pack it into pouch, the four day is giving the pack of instant ginger drink to the community around. After the socialization, KKN Panca Marga University Probolinggo team in Paiton district expect the community to have a higher immunity health rate and is able to use instant ginger drink as a business opportunity for housewives, therefore it can indirectly improve the prosperity of community in Sukodadi Village Paiton District in the period of pandemic Covid-19.